KIF5A p.Pro986Leu Risk Variant and Accelerated Progression of Amyotrophic Lateral Sclerosis - Arianna Manini; Rosario Vasta; Alberto Brusati; Francesco Scheveger; Silvia Peverelli; Alessio Maranzano; Alberto Doretti; Francesco Gentile; Eleonora Colombo; Maura Brunetti; Cristina Moglia; Antonio Canosa; et al. (Annals of Clinical and Translational Neurology)
ABSTRACT This study explored the impact of KIF5A rs113247976 (p.Pro986Leu), a risk allele for amyotrophic lateral sclerosis (ALS), on phenotypic variability in two Italian ALS cohorts (discovery, n = 865; replication, n = 1174). The minor allele (T) frequency was 0.015. No patients were homozygous (TT), allowing comparison between wild type and heterozygous carriers only. Heterozygous carriers showed faster disease progression (ALSFRS‐R preslope). Findings were validated across both cohorts. Multiple linear regression identified p.Leu986 and age at onset as ALSFRS‐R preslope predictors. In conclusion, heterozygous p.Leu986 in KIF5A is associated with faster ALS progression, supporting its consideration for genetic screening in clinical trials.